Liposome-loaded chitosan physical hydrogel: Toward a promising delayed-release biosystem. (22nd January 2015) - Billard, Aurélien; Pourchet, Léa; Malaise, Sébastien; Alcouffe, Pierre; Montembault, Alexandra; Ladavière, Catherine
Graphical abstract: Highlights: Development of a biosystem entirely biocompatible and biodegradable. "Hybrid" system composed of phosphatidylcholine liposomes entrapped within a chitosan physical hydrogel. Confirmation of the presence of liposomes within the hydrogel by cryo-SEM. Proof of concept of delayed-release by using a model water soluble molecule (carboxyfluorescein, CF) encapsulated in liposomes, themselves incorporated into the chitosan hydrogel. Abstract: This work deals with the elaboration of an original biosystem in view of its application as drug delayed-release device in biomedical area. This innovative "hybrid" system is composed of phosphatidylcholine liposomes entrapped within a chitosan physical hydrogel (only constituted of polymer and water). To this end, pre-formed liposomes were suspended into chitosan solutions, and the polymer gelation process was subsequently carried out following particular experimental conditions. This liposome incorporation did absolutely not prevent the gel formation as shown by rheological properties of the resulting tridimensional matrix. The presence of liposomes within the hydrogel was confirmed by fluorescence and cryo-scanning electron microscopies. Then, the expected concept of delayed-release of this "hybrid" system was proved using a model water soluble molecule (carboxyfluorescein, CF) encapsulated in liposomes, themselves incorporated into the chitosan hydrogel. The CF release was assayed after repeated and intensive washings of hydrogels, and was found to be higher in the CF-in-hydrogel systems in comparison with the CF-in-liposomes-in-hydrogel ones, demonstrating a CF delayed-release thanks to lipid vesicles.